Pelaksanaan Perjanjian Pekerjaan Jalan Antara Dinas Pekerjaan Umum dan CV. Citra Ngada di Kecamatan Bajawa Kabupaten Ngada - Hendrika Yunita Bebhe; Orpa J. Nubatonis; Chatryen M. Dju Bire (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This study aims to find out and discuss the implementation of the road work agreement between the Public Works Office and Cv. Citra Ngada in Bajawa District, Ngada Regency. The research is an empirical research supported by primary data, secondary data and tertiary data. This study used data collection techniques in the form of literature studies and interviews with three respondents. This study uses data analysis techniques in the form of editing, coding and systemaging as well as qualitative descriptive data analysis. The results of this study show (1) the implementation of the Agreement between CV. Citra Ngada and the Public Works Office are carried out based on Presidential Regulation Number 12 of 2021 concerning the Procurement of Government Goods/Services. During the duration of the Segment Log Work Agreement, there was a change in work where there was a difference between the field conditions and the frame of reference specified in the contract document (2) Obstacles in the implementation of road works between the Public Works Office and CV Citra Ngada were greatly influenced by various internal and external factors. Bad weather, equipment breakdowns, labor shortages, and material procurement issues.